African Spelling Book - Loy, Angelo (AMREF, 2005)
Coproduction: Kenya, Italy. Verzio Film Festival Submission 2007. A series of short films written, narrated and filmed by a group of boys and girls living in the slums of Nairobi, Kenya. Each story refletcts their point of view on life in Kenya, and gives the viewer a unique chance to explore their world